Formation of Student Character Through Regional Culture at 01 Nisam Elementary School, North Aceh Regency - Alawiyah, Alawiyah; Fitrah, Hariki; Khairani, Cut (Postgraduate School, Universitas Negeri Padang, 2023)
This study aims to analyze the implementation of students' character building through the Ranup Lampuan dance and the Maulod Festival at Elementary School (ES) 01 Nisam and to analyze the values contained in the Ranup Lampuan dance and the Maulod Festival for the character building of students at ES 01 Nisam. The method used in this study is a qualitative method with an ethnographic approach. The research subjects are school principals, teachers, and students. Sources of data were obtained from primary data, namely data directly obtained from informants and also secondary or supporting data (documentation of student activities). Data analysis used 1) domain analysis; 2) taxonomic analysis; 3) componential analysis; and 4) cultural theme analysis. The research findings are 1) The implementation of student character formation through the Ranup Lampuan dance is part of extracurricular activities, in which the activity is guided by the teacher. while the Kenduri Maulod tradition is a celebration in commemoration of the birthday of the Prophet Muhammad SAW which is held in the month of Rabi’ul Awal to Rabi'ul Akhir. At ES 01 Nisam, the Kenduri Maulod celebration is carried out with various activities such as Dzikee and praying together; and 2) in the Ranup Lampuan dance there are several character values such as respect values, creative values, responsibility values, and cultural values. Meanwhile, in the Kenduri Maulod tradition, there are character values, namely the value of Islamic Ukhuwah, exemplary values, religious values, and social values.